Comprehensive study on the influence of molybdenum substitution on characteristics and catalytic performance of magnetite nanoparticles - Rahim Pouran, Shima; Bayrami, Abolfazl; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan; Shafeeyan, Mohammad Saleh; Khataee, Alireza (Springer Verlag, 2018)
We prepared a number of heterogeneous catalysts by exchanging the structural iron of magnetite with molybdenum ions. To obtain the optimum value, Mo at various concentrations was coprecipitated with iron species (Fe3−x Mo x O4, x = 0.028, 0.069, 0.13, and 0.21). Characterization revealed that all the samples had inverse spinel structure with excellent stability and magnetic properties. Higher Mo contents (x = 0.13 and 0.21) significantly improved the specific surface area of magnetite, leading to higher capacity for methylene blue (MB) adsorption. The catalytic performance of the samples for degradation of MB solution through Fenton reaction was then assessed. The Fe2.62Mo0.21O4 sample showed substantial activity, removing MB completely within 150 min. This enhanced activity is discussed based on the enlarged surface area, the role of surface Mo4+/Mo6+ redox pairs, and oxygen vacancies. Kinetic studies revealed that MB degradation by Fe3−x Mo x O4 nanoparticles in presence of H2O2 was well fit by a zeroth-order kinetics model. These results support use of such Fe3−x Mo x O4 materials as active magnetically separable heterogeneous catalysts, capable of degrading various contaminants through Fenton reaction.